Influence of size and plant growth regulators on corm and cormel production of gladiolus (Gladiolus grandiflorus L.) - Rashid, MHA (Progressive Agriculture, 2018)
Gladiolus is an excellent cut flower grown throughout the world for its spikes with florets of massive form, brilliant colours, attractive shapes, varying size and long shelf life. However, major constraint for gladiolus cultivation is the corm dormancy. Plant growth regulators (PGRs) play an important role in breaking dormancy and promote more number of quality corm and cormel productions in gladiolus. Therefore, an experiment was conducted to study the influence of corm size and plant growth regulators on corm and cormel production of gladiolus during the period from October 2017 to April 2018 at the Landscaping section of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh. The two-factor experiment included two corm sizes viz., 3-4 cm and 4.1-5 cm, and two PGRs viz., GA3 @ 250, 500 and 750 ppm; and NAA @ 100, 200 and 300 ppm along with tap water as control. The experiment was laid out in a randomised complete block design (RCBD) with three replications. The results revealed that the corm size and PGRs at different concentrations significantly influenced the corm and cormel producing attributes of gladiolus. Maximum number of corms and cormels per plant, maximum weight of single corm, maximum weight of corms and cormels per plant, biggest size of single corm, highest yield of corms and cormels per hectare were recorded from 4.1-5 cm sized corms and GA3 @ 500 ppm, compared to rest of the treatments. It was observed that combined treatments had significant influence on all the parameters studied. The treatment combination of 4.1-5 cm sized corms and GA3 @ 500 ppm was found to be best in terms of corm and cormel production of gladiolus. Progressive Agriculture 29 (2): 91-98, 2018